Vpliv epigenetskih modifikacij na razvoj in funkcijo moške gamete - Jan, Žiga (Medicinski razgledi, 2008)
Epigenetic DNA modifications participate in genome regulation. These marks modulate the gene expression pattern and, on the whole genome scale, provide acell-specific expression profile.'fhey are pivotal to development, as they first enable preimplantation embryo pluripotency and, later on, cell differentiation.13ecause these marks are dynamic, they allow for the development of germ cell. In this review, DNA methylation, histone modifications and RNA interference are presented and their possible role in male germ cell development is discussed. Some early evidence linking erroneousepigenetic marks to male gamete (spermatozoon) dysfunction is also presented.
Keywords: Genomsko vtisnenje; Spermatogenesis; Gensko izražanje; Dna Methylation; Gene Expression; Histoni; Spermatogeneza; Histones; Genomic Imprinting; DNA, metilacija; genom; DNA; izražanje genov